Concerto para saxofone Ibira Guira Recê de Edmundo Villani-Côrtes (1930): sua gênese, seus aspectos estruturais e interpretativos, sua aplicabilidade pedagógica e sua edição - Paulo Eduardo Souza de Almeida (2020)
The aim of this dissertation is to present information about the concert for saxophone Ibira Guira Recê by Edmundo Villani-Côrtes (1930), with the following structure: the genesis of the concert, its structural and interpretative aspects, its pedagogical applicability and its edition. The study was structured in four parts: a brief history of the saxophone since the time of Brazilian Empire to the Nova República and the reflections on the instrument in higher education as well as in publications; current information about the composer; studies and analyzes on the structure and interpretation of the Ibira Guira Recê concert, with notes on its didactic applicability; and the critical edition of the piece with changes recently made by the composer. Based on this study, we pointed the unique and transparent writing of Villani-Côrtes, which reveals his tastes and lifestyle, as well as the significance of the piece for the Brazilian repertoire of saxophone.